The political humanism of Hannah Arendt - McCarthy, Michael H., 1942- (Lexington Books, 2012)
This critical study of Arendt explores the sources and dangers of political alienation in the West from the citizen republics of classical antiquity to the consumer societies of modern liberal democracies. It is a sympathetic appraisal of the high promise and great perils of the political life (the bios politikos).